2022
DOI: 10.1094/pdis-06-21-1142-re
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide Sensitivity of Colletotrichum Species Causing Bitter Rot of Apple in the Mid-Atlantic U.S.A.

Abstract: Apple growers in the Mid-Atlantic region of the United States have reported increased losses to bitter rot of apple. We tested the hypothesis that this increase is because the Colletotrichum population has developed resistance to commonly used single-mode-of-action (single-MoA) fungicides. We screened 220 Colletotrichum isolates obtained from 38 apple orchards in the Mid-Atlantic region for resistance to 11 fungicides in FRAC (Fungicide Resistance Action Committee) groups 1, 7, 9, 11, 12, and 29. Eleven (5%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Since different Alternaria and Colletotrichum species have different sensitivity toward the commercially available and routinely applied fungicides [ 10 , 11 , 12 , 72 , 73 ], the complete and precise knowledge of the species involved in the etiology of heart rot and anthracnose of pomegranate fruits is the first step toward devising effective management strategies aimed at preventing these two major fungal diseases of pomegranate in India.…”
Section: Resultsmentioning
confidence: 99%
“…Since different Alternaria and Colletotrichum species have different sensitivity toward the commercially available and routinely applied fungicides [ 10 , 11 , 12 , 72 , 73 ], the complete and precise knowledge of the species involved in the etiology of heart rot and anthracnose of pomegranate fruits is the first step toward devising effective management strategies aimed at preventing these two major fungal diseases of pomegranate in India.…”
Section: Resultsmentioning
confidence: 99%
“…Three commonly used fungicides were used for sensitivity analyses: chlorothalonil (Haack et al, 2018), pyraclostrobin (Usman et al, 2021) and thiophanate‐methyl (Martin et al, 2021). For C .…”
Section: Methodsmentioning
confidence: 99%
“…Three commonly used fungicides were used for sensitivity analyses: chlorothalonil (Haack et al, 2018), pyraclostrobin (Usman et al, 2021) and thiophanate-methyl (Martin et al, 2021). For C. tenuissimum YCW977, 50% effective concentration (EC 50 ) values were determined using mycelial growth assays.…”
Section: Fungicide Sensitivity Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of only a few effective fungicides to control Colletotrichum pathogens and the persistent threat of fungicide resistance development in the pathogens make management of bitter rot of apples a difficult task (Dowling et al 2020). Previous studies have reported variability in fungicide efficacy against bitter rot, which is, to a large extent, related to differences in fungicide sensitivity among Colletotrichum species and efficacy among fungicide active ingredients (Chechi et al 2019;Khodadadi et al 2020;Martin et al 2022;Munir et al 2016). Differences in fungicide sensitivity among species from a single geographical location may be inherent or may have emerged because of fungicide selection pressure influenced by the species-specific inoculum frequency and density and the influx of wild-type phenotypes from nearby hosts (Chen et al 2016).…”
mentioning
confidence: 99%